Frontispiece: Direct Epoxidation of Propylene over Stabilized Cu+ Surface Sites on Titanium‐Modified Cu2O. Issue 41 (5th October 2015) - Yang, Xiaofang; Kattel, Shyam; Xiong, Ke; Mudiyanselage, Kumudu; Rykov, Sergei; Senanayake, Sanjaya D.; Rodriguez, José A.; Liu, Ping; Stacchiola, Dario J.; Chen, Jingguang G.
<x xml:space="preserve">Abstract</x> Propylene Epoxidation Catalysts. Cu+ active sites on a Cu2O surface are stabilized with TiOx. J. G. Chen et al. show in their Communication on page 11946 ff. that the resulting mixed oxide helps form an oxametallacycle intermediate with propylene giving higher selectivity for propylene epoxidation.